Clinical trial of the D.E.L.P.H.I.N. speech treatment for children and adolescents who stutter. (2nd October 2018) - Keilmann, Annerose; Neumann, Kirsten; Zöller, Daniela; Freude, Christina
Abstract: Purpose: The present trial investigated the D.E.L.P.H.I.N. (Deblockierungsimpuls, Entspannung, Logopädie, Phonetik, Hör-Wahrnehmungstraining, Intensität, nasaler Schwingungsakzent) speech treatment for children and adolescents who stutter, an approach using fluency shaping with an intensive time schedule and group sessions. Methods: Participants were 42 male and 14 female persons who stuttered with a median age of 13.0 years. Participants and their parents completed the strength and difficulties questionnaire at the beginning of the therapy and 1 year later. Participants completed the Speech Questionnaire, an instrument to measure the impact of stuttering, twice before and twice after completing the therapy. The stuttering rate and mean length of the three longest stuttering events were studied four times in videos of interviews, reading texts and three telephone calls. Outcomes are reported for the 56 children and young adults who stuttered and who completed D.E.L.P.H.I.N. The main analysis was performed using linear mixed models. Results: Quality of life as measured in the Strength and Difficulties Questionnaire (SDQ) – filled in by the participants/their parents – increased significantly from before the start of the therapy to 1 year after completion of the therapy. The subjective rating of the impact of stuttering also improved significantly. The stuttering rate and mean length of the longest stuttering event decreased significantly for all three modes from pre-treatment to 12 months post-treatment. Conclusions: After D.E.L.P.H.I.N., a significant improvement of the relevant endpoints quality of life, impact of stuttering, and severity of stuttering is observed.